Investigating the Provenance of Iron Artifacts of the Royal Iron Factory of São João de Ipanema by Hierarchical Cluster Analysis of EDS Microanalyses of Slag Inclusions - Mamani-Calcina,Elmer Antonio (2017)
Microstructural characterization techniques, including EDX (Energy Dispersive X-ray Analysis) microanalyses, were used to investigate the slag inclusions in the microstructure of ferrous artifacts of the Royal Iron Factory of São João de Ipanema (first steel plant of Brazil, XIX century), the D. Pedro II Bridge (located in Bahia, assembled in XIX century and produced in Scotland) and the archaeological sites of São Miguel de Missões (Rio Grande do Sul, Brazil, production site of iron artifacts, the XVIII century) and Afonso Sardinha (São Paulo, Brazil production site of iron artifacts, XVI century). The microanalyses results of the main microconstituents of the microstructure of the slag inclusions were investigated by hierarchical cluster analysis and the dendrogram with the microanalyses results of the wüstite phase (using as critical variables the contents of MnO, MgO, Al2O3, V2O5 and TiO2) allowed the identification of four clusters, which successfully represented the samples of the four investigated sites (Ipanema, Sardinha, Missões and Bahia). Finally, the comparatively low volumetric fraction of slag inclusions in the samples of Ipanema (~1%) suggested the existence of technological expertise at the ironmaking processing in the Royal Iron Factory of São João de Ipanema.